Legal Politics of The Formation of Regional Regulations Based on Positive Law - Juanda, Juanda; Juanda, Ogiandafiz (Jurnal Dinamika Hukum, 2022)
The title of this research is the legal politics of the formation of regional regulations based on positive law. The formulation of problem is how the legal politics of the formation of regional regulations based on positive law in Indonesia? The methods of the research: 1. The type of research is normative. 2. The approach used is a legal approach and is complemented by a political approach. 3. The legal materials used are primary and secondary legal materials. 4. The method of analysis is a qualitative juridical analysis. The results of the research indicate that the legal politics of the formation of regional regulations is part or a sub-system of the legal politics of the formation of national legislation (national law). The legal politics of the formation of regional regulations is not only bound and guided by the basis of state philosophy, theory, Unitary form of state, principles, content material, statutory regulations, but can also contain material on the implementation of regional autonomy, co-administration tasks, further elaboration, provisions of higher laws and regulations. Furthermore, it may also contain local content material in accordance with the provisions of laws and regulations. In addition, the legal politics of the formation of regional regulations seeks to strengthen the unitary state and actualize regional regulations that are aspirational, responsive, accountable, efficient, effective and functional.Keywords: legal politics, formation, regional regulations